2014
DOI: 10.3201/eid2011.131315
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Illness, Australia, Circa 2000 and Circa 2010

Abstract: Overall incidence of foodborne gastroenteritis declined but remains high, and the incidence of salmonellosis and campylobacteriosis increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 21 publications
1
119
0
1
Order By: Relevance
“…These outbreaks translate to a significant economic impact to the affected industries, in addition to the medical burden caused to the affected individuals 7,8 .…”
Section: Salmonella Infections In Australiamentioning
confidence: 99%
“…These outbreaks translate to a significant economic impact to the affected industries, in addition to the medical burden caused to the affected individuals 7,8 .…”
Section: Salmonella Infections In Australiamentioning
confidence: 99%
“…Warmer temperatures facilitate the reproduction and replication of pathogens, enabling quicker reproduction in shorter periods of time [92]. For example, Campylobacter grows optimally at [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] • C and can double in number in just 6 hours at 32…”
Section: Pathogenmentioning
confidence: 99%
“…Campylobacteriosis shows seasonal trends globally. A systematic review of more than 15 countries including Australia found campylobacteriosis incidence consistently peaked in spring to summer [14,17,37,[104][105][106] suggesting a seasonal association. Indeed, a study in Massachusetts, US, found that campylobacteriosis cases peaked within a two-day window of the warmest temperatures of the year [107], and outbreaks of campylobacteriosis in South Korea were strongly positively correlated with the monthly mean temperature (r = 0.66) [108].…”
Section: Humansmentioning
confidence: 99%
See 2 more Smart Citations